Doping and annealing effects on structural, optical and electrical characteristics of Sn-doped ZnS thin film - Md Abu Sayeed; Hasan Khaled Rouf; Kazi Md Amjad Hussain (Materials Research Express, 2021)
This work presents the fabrication of Zn _1−x S:Sn _x thin films using the chemical bath deposition method and investigates the effects of Sn doping and annealing temperature on the structural, optical and electrical properties of ZnS thin films. The XRD patterns show that the relative intensities of the major diffraction peaks increase with Sn dopant incorporation and annealing temperature. Because high-temperature annealing forms several nucleation centers throughout the lattice and dopant incorporation enhances point defects leading to crystallite boundary mobility enhancement, crystallinity is also improved. UV–vis-NIR spectrophotometric studies revealed that the films have good transmittance that is larger than 75% in both visible and near-infrared regions and their optical bandgap ranges from 3.34 eV to 3.90 eV. Both the Sn content and annealing temperature cause the transmittance and the optical bandgap to rise. The absorption edge shifts towards the longer wavelength for higher Sn contents and annealing temperatures. Also, the decreased Urbach energy with increased Sn content or annealing temperature can be attributed to the reduced structural disorders and dislocations of ZnS crystals that are indicated by improved crystallinity. Electrical characterization by the two-point probe method exhibits that at higher annealing temperature grain boundary scattering limits the number of mobile carriers by increasing interatomic binding. On the other hand, due to increased carrier concentration and decreased dislocations resulting from the Sn content or annealing, localized carriers dominate in the bulk crystal state and require higher activation energy to replace an interstitial atom and excite the bulk states.